2019
DOI: 10.1016/j.eneco.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The impact of FDI on regional air pollution in the Republic of Korea: A way ahead to achieve the green growth strategy?

Abstract: Can FDI help to reduce regional air pollution emissions in Korea? Given the proclamation of a far-reaching national green growth strategy that requires a shift in public and private investments, this paper addresses the need for empirical estimates on the environmental consequences of FDI inflows into Korea. Using a simultaneous equations model the impacts of FDI inflows are decomposed into direct as well as indirect scale, composition, and technique effects. Thereby, the analysis utilizes panel data on six ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(66 citation statements)
references
References 46 publications
5
59
1
1
Order By: Relevance
“…Our results are in contrast with the study of Merican et al (2007) which found that there is no impact of foreign direct investment on carbon emission in context of Singapore. Our results are also contrary with the study of Hille et al (2019) explored the impact of FDI on air pollutions in Korea and found that FDI stimulates regional economic growth and reduces air pollution.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are in contrast with the study of Merican et al (2007) which found that there is no impact of foreign direct investment on carbon emission in context of Singapore. Our results are also contrary with the study of Hille et al (2019) explored the impact of FDI on air pollutions in Korea and found that FDI stimulates regional economic growth and reduces air pollution.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, Hille et al (2019) 2018to test cointegration. Their findings have shown that FDI impedes environmental quality by increasing carbon emissions.…”
Section: Fdi-emissions Nexusmentioning
confidence: 99%
“…As economic factors in our model, both PGDP and FDI can represent regional economic development ( Jiang et al, 2018 ;Hille et al, 2019 ). Based on the OLS results, PGDP has been identified as one of the crucial factors resulting in NGEC increase ( Amri, 2017 ;Ding et al, 2017 ), while FDI shows a minor negative effect on national NGEC, which is similar to the conclusion of Jiang et al (2018) .…”
Section: The Spatial Effects Of Economic Factors On Ngecsupporting
confidence: 55%
“…Besides economic growth, factors influencing the pollution level include, among others, institutional quality and democracy ( Tamazain and Rao, 2010 ; You et al., 2015 ), financial development ( Nasir et al., 2019 , Pham et al. 2020 ), trade measures such as trade openness and FDI ( Hille and Shahbaz, 2019 ; Hille et al., 2019 ), urbanization ( Pham et al., 2020 ), transportation ( Nassani et al., 2017 ), general as well as energy innovations ( Shahbaz et al., 2018a ; Yang et al., 2014 ), and government environmental expenditures ( Hille and Lambernd, 2020 ). Although existing studies also treated financial development as an important determinant in pollution modelling, ambiguous results are reported ( Zaidi et al., 2019 ).…”
Section: Theoretical Construction Methodology and Datamentioning
confidence: 99%